(untitled) (Iraqi Journal of Medical Sciences, 2021)
Background: Premarital blood screening helps couples to identify potential health problems and risks for themselves and their offspring, considered a primary preventive approach for couples planning for conception and an important step towards protecting society from spread of diseases especially thalassemia, and allowing people to enjoy life. Objective: To determine the prevalence of minor ?-thalassemia, human immunodeficiency virus (HIV), hepatitis B virus (HBV), hepatitis C virus (HCV) and venereal disease research laboratory (VDRL) referred to Al-Nuaman Teaching Hospital. Methods: The cross-sectional study as part of premarital screening in Al-Nuaman Teaching Hospital was conducted over six months from May 2017 to the end of October 2017. Total individual of 3027 underwent routine mandatory tests. Results: Regarding HIV and VDRL cases were zero, regarding HBV was no case in August, only one case in May and June, two cases in September and October, and four cases in July, regarding HCV there was no cases in May, June and Aug., two cases in September, and October, and three cases in July, Regarding ?-thalassemia minor, one couple in August and another couple in September, those two couples both male and female were thalassemia minor , while the rest either the male or female were thalassemia minor. Conclusion: Premarital screening program is an important project in detecting asymptomatic carriers of hepatitis viral infection and thalassemia. This study showed that incidence of hepatitis B infections 0.33% were more frequent than Hepatitis C infections 0.23%, there was no cases of HIV infection detected so far, and ?-thalassemia trait prevalence was 1.92%. Keywords: Premarital, ?-thalassemia, virology, screening Citation: Hanoon BD, Sudad A. Khalf SA, Khalaf IA. Premarital screening program in Al-Nuaman Teaching Hospital. Iraqi JMS. 2021; 19(2): 147-151. doi: 10.22578/IJMS.19.2.3